Impairment of Glucose Metabolism and Suppression of Stemness in MCF-7/SC Human Breast Cancer Stem Cells by Nootkatone - Yen Thi-Kim Nguyen; Ngoc Bao To; Vi Nguyen-Phuong Truong; Hee Young Kim; Meran Keshawa Ediriweera; Yoongho Lim; Somi Kim Cho (MDPI AG, 2022)
Targeting cancer stem cell metabolism has emerged as a promising therapeutic strategy for cancer treatment. Breast cancer stem cells (BCSCs) exert distinct metabolism machinery, which plays a major role in radiation and multidrug resistance. Therefore, exploring the mechanisms involved in energy utilization of BCSCs could improve the effectiveness of therapeutic strategies aimed at their elimination. This study was conducted to clarify the glucose metabolism machinery and the function of nootkatone, a bioactive component of grapefruit, in regulating glucose metabolism and stemness characteristics in human breast carcinoma MCF-7 stem cells (MCF-7SCs). In vivo experiments, transcriptomic analysis, seahorse XF analysis, MTT assay, Western blotting, mammosphere formation, wound healing, invasion assay, flow cytometric analysis, reverse transcription-quantitative polymerase chain reaction, and in silico docking experiments were performed. MCF-7SCs showed a greater tumorigenic capacity and distinct gene profile with enrichment of the genes involved in stemness and glycolysis signaling pathways compared to parental MCF-7 cells, indicating that MCF-7SCs use glycolysis rather than oxidative phosphorylation (OXPHOS) for their energy supply. Nootkatone impaired glucose metabolism through AMPK activation and reduced the stemness characteristics of MCF-7SCs. In silico docking analysis demonstrated that nootkatone efficiently bound to the active site of AMPK. Therefore, this study indicates that regulation of glucose metabolism through AMPK activation could be an attractive target for BCSCs.